Lateral pharyngotomy extended by resection of the mandibular angle-an alternative approach to the surgical treatment of oropharyngeal (tonsillar) cancers - Čoček, Aleš; Průcha, Ivan; Hahn, Aleš (Acta oto-laryngologica, 2009)
CONCLUSION: The authors found the procedure, when used with the proper indications, to be an uncomplicated and expeditious method that presents little risk to surrounding structures, has no residual cosmetic or functional consequences for the patient, presents a low risk of complications, and has a good oncological outcome. The main indications for this procedure are related to the extent of the tumour and the surgeon's experience with the method.
Keywords: dospělí; Carcinoma, Squamous Cell; mandibula; Female; Adult; ženské pohlaví; lidé; Mandible; nádory orofaryngu; pooperační komplikace; farynx; adjuvantní radioterapie; Male; Postoperative Complications; Aged; Oropharyngeal Neoplasms; spinocelulární karcinom; Radiotherapy, Adjuvant; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Pharynx; Humans